The Role of Social Media in Increasing the Competitiveness of MSMEs in Halal Local Products Case Study of Carica Gemilang - Rijawanto, Subri; Kharisma, Nurul; Septiani, Kharisma; Sabrina, Laila (Proceedings Series on Social Sciences & Humanities, 2025)
This research discusses the role of social media in increasing the income and competitiveness of MSMEs with Carica Gemilang halal local products in Wonosobo. Before utilizing social media, Carica Gemilang MSMEs experienced difficulties in expanding the market and increasing revenue due to limited access to traditional marketing. The purpose of this study is to evaluate the impact of social media use on the income and competitiveness of MSMEs, especially halal products. The research was conducted through descriptive qualitative case studies with interviews, analysis of social media content, and direct observation. The results of the study show that social media plays an important role in increasing Carica Gemilang's revenue through promotions and wider interaction with consumers. Product competitiveness also increases due to the ease of promoting the advantages of halal products in a competitive market. Thus, social media is an effective tool for MSMEs in increasing the income and competitiveness of halal products in the digital era.